Healing progression of tail docking and ear tag wounds in lambs - Jocelyn M. Woods; Sarah J. J. Adcock (Scientific Reports)
Abstract Tail docking and ear tagging are common husbandry practices in lambs, but little is known about subsequent wound healing or how it may be affected by performing both procedures concurrently. Our objectives were to: (1) describe wound healing following tail docking and ear tagging, and (2) compare healing of ear wounds in docked and undocked lambs. Within 28 female Polypay twin pairs, one lamb was docked using a rubber ring between 1 and 2 days of age and the other lamb’s tail was left intact. Tags were attached to both ears of all lambs. We photographed tail and ear wounds twice weekly until weaning (mean ± SD; 64 ± 5 days of age). Tail wounds took 43 ± 9 days to heal (range: 30–60 days). Pus, a sign of infection, was present at least once in 89% of tail wounds and was associated with delayed healing. Only 49% of ear wounds had healed by weaning, and tail docking did not predict the probability of healing. Pus and sanguineous exudate (i.e., bleeding) were present at least once in 21% and 96% of ear wounds, respectively. Pus was not associated with the probability of ear wound healing, but ears with more frequent bleeding were less likely to have healed by weaning. The duration of healing and likelihood of infection following both procedures raise welfare concerns and suggest refinements or alternatives are warranted.